2021
DOI: 10.3389/fnagi.2021.764334
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis Between Neutrophil-to-Lymphocyte Ratio on Admission and Development of Delirium Among Older Hospitalized Patients With COVID-19

Abstract: Objective: To examine any prospective association between neutrophil-to-lymphocyte ratio (NLR) at hospital admission and subsequent delirium in older COVID-19 hospitalized patients comparing by sex and age groups.Methods: The sample consisted of 1,785 COVID-19 adult inpatients (minimum sample size required of 635 participants) admitted to a public general hospital in Madrid (Spain) between March 16th and April 15th, 2020. Variables were obtained from electronic health records. Binary logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Booka et al [ 24 ] suggested that patients older than 70 years were at higher risk of developing postoperative delirium. Recently, NLR has proved to be a good predictor of delirium during hospitalization of COVID-19 patients, especially older adults, while SII could not predict delirium development in their study [ 25 ]. In our study, no significant difference in cardiovascular complication or delirium occurrence was observed using the postoperative SII cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…Booka et al [ 24 ] suggested that patients older than 70 years were at higher risk of developing postoperative delirium. Recently, NLR has proved to be a good predictor of delirium during hospitalization of COVID-19 patients, especially older adults, while SII could not predict delirium development in their study [ 25 ]. In our study, no significant difference in cardiovascular complication or delirium occurrence was observed using the postoperative SII cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patients with delirium were four times more likely to die than those without delirium [ 14 ]. Similarly, a meta-analysis of nine studies showed that the death rate in COVID-19 patients with delirium was twice as high as those without delirium [ 13 17 ]. In this scenario, the unique social factors of an unprecedented pandemic, such as self-isolation and limited family visits, may have negatively impacted on the management of delirium [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the incidence of delirium in critically ill patients with COVID-19 is very high, reaching more than 50% ( Pun et al, 2021 ; Williamson et al, 2022 ). In particular, delirium is also known as a strong predictor of mortality in hospitalized COVID-19 patients ( Fernández-Jiménez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%